2015
DOI: 10.1002/ana.24345
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐specific immunoglobulin M bands in cerebrospinal fluid are associated with a reduced risk of developing progressive multifocal leukoencephalopathy during treatment with natalizumab

Abstract: The presence of IgM bands reflects a process that may diminish the risk of PML by counteracting the excess of immunosuppression that may occur during natalizumab therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 29 publications
0
38
0
2
Order By: Relevance
“…Use of serum and cerebrospinal fluid JCV antibody indices, measurement of L-selectin expressing CD4 T cells, and other methods may further refine risk stratification. [108][109][110][111] A JCV antibody index below 0.9 is associated with lower risk for PML and an index above 1.5 is associated with higher risk, 109 but observational studies found that natalizumab treatment was associated with increasing indices over time (0.091 units/year, or 13%) and high annual seroconversion rates (8.5-10.3%). 112 113 Alternative treatments should be considered for patients who seroconvert.…”
Section: Mitoxantronementioning
confidence: 99%
“…Use of serum and cerebrospinal fluid JCV antibody indices, measurement of L-selectin expressing CD4 T cells, and other methods may further refine risk stratification. [108][109][110][111] A JCV antibody index below 0.9 is associated with lower risk for PML and an index above 1.5 is associated with higher risk, 109 but observational studies found that natalizumab treatment was associated with increasing indices over time (0.091 units/year, or 13%) and high annual seroconversion rates (8.5-10.3%). 112 113 Alternative treatments should be considered for patients who seroconvert.…”
Section: Mitoxantronementioning
confidence: 99%
“…Moreover, some studies suggested that CSF OCBs of the IgM isotype associate with (a) aggressive MS forms [18], (b) better responses to immunotherapies [19], (c) lower risks of developing progressive multifocal leukoencephalopathy in patients on natalizumab [20], and (d) higher probability of reaching EDSS scores of 3.0/4.0 10 years after onset [21]. The data are waiting for further confirmation and wider consensus before IgM OCB test enters routine clinico-laboratory practice [22].…”
Section: Multiple Sclerosis and Oligoclonal Bandsmentioning
confidence: 99%
“…Even for some time after the cessation of natalizumab, a certain risk of PML remains and pharmacovigilance should be continued [63,64]. There are increasing efforts to further refine PML risk stratification, especially for patients that convert to anti-JCV antibody positive status while on natalizumab, using antibody indices in serum and cerebrospinal fluid, as well as other approaches [65][66][67][68].…”
Section: Natalizumabmentioning
confidence: 99%